1996
DOI: 10.1046/j.1537-2995.1996.36996420762.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of very low doses of subcutaneous recombinant human erythropoietin in facilitating autologous blood donation before orthopedic surgery

Abstract: Subcutaneously administered rHuEPO at a dose of 100 IU per kg twice a week for 2 weeks is effective in facilitating the collection of blood for autologous use and may improve the cost-benefit ratio of blood conservation interventions. Doses < or = 60 IU per kg are ineffective in facilitating such collections in this surgical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Clinical trials of ESA have also demonstrated a dose‐response relationship between EPO and RBC expansion 27 . A study of “very low” dose EPO therapy in autologous blood donors found that 400 U/kg administered over a 2‐week interval resulted in clinically significant erythropoiesis 28 . As shown in Table 2, 24,27,29‐31 patients treated with ESA therapy during aggressive autologous blood phlebotomy had 358 to 1102 mL (28%‐48% RBC) expansion over 25 to 35 days, or the equivalent of 2 to 5 blood units.…”
Section: Functional Iron Deficiencymentioning
confidence: 99%
“…Clinical trials of ESA have also demonstrated a dose‐response relationship between EPO and RBC expansion 27 . A study of “very low” dose EPO therapy in autologous blood donors found that 400 U/kg administered over a 2‐week interval resulted in clinically significant erythropoiesis 28 . As shown in Table 2, 24,27,29‐31 patients treated with ESA therapy during aggressive autologous blood phlebotomy had 358 to 1102 mL (28%‐48% RBC) expansion over 25 to 35 days, or the equivalent of 2 to 5 blood units.…”
Section: Functional Iron Deficiencymentioning
confidence: 99%
“…(2002) showed that patients who had predonated autologous blood had lower Hb levels on admission, and higher likelihood of having autologous transfusion. Use of recombinant erythropoietin and iron during PAD has been reported to increase red cell production (Mollmann et al ., 1995; Price et al ., 1996), the number of autologous units donated (Price et al ., 1996; Sans et al ., 1996), and to reduce patient exposure to allogeneic blood (Price et al ., 1996).…”
mentioning
confidence: 99%
“…[40][41][42][43][44] The use of autologous donation and erythropoietin in patients with inadequate estimated red cell reserve and life expectancy >10 years is a cost-effective strategy for blood conservation. [45][46][47][48][49] Autologous donation is more cost-effective than allogeneic transfusion ($856 and $892 vs. $1769 and $1352 per unit for THA and TKA, respectively). 49 Autologous donation is also beneficial in that the risk of deep vein thrombosis is reduced.…”
Section: Management Of Blood Loss and Transfusionmentioning
confidence: 99%